Effect of laser energy on grain size of cadmium oxide nanoparticles in ethanol by PLD method - Rasha H. Ahmed; Abdul Majeed E. Ibrahim; Kadhim A. Aadem (Tikrit Journal of Pure Science)
The  Pulse laser deposition technique was used in the preparation of nanoparticle solutions (CdO) using Nd:YAG laser and five deposition energies (400, 500, 600, 700 and 800 mJ) with fixed pulses (300 pulse and 6 Hz) was used .